HARNESSING EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CULTURE FOR EMPLOYEE RETENTION IN THE NGO OF WOMEN EMPOWERMENT - Widiya Avianti; Endang Pitaloka (Journal of Economic Empowerment Strategy (JEES), 2023)
This research was conducted at the Women Empowerment Foundation, focusing on employee retention, believed to have different dynamics compared to profit-oriented companies. The foundation, as a Non-Governmental Organization (NGO) with social goals, often faces financial uncertainty that can affect job stability. The purpose of the study is to determine how, if at all, organizational culture and employee engagement affect foundation employee retention. The research method employed was quantitative, with a survey approach using a questionnaire as the research instrument. Respondents were permanent employees of the foundation with a minimum of one year of experience. The total number of respondents involved was 86 individuals. Multiple linear regression analysis revealed that employee engagement and organizational culture positively influence employee retention at the Women Empowerment Foundation. Specifically, employee engagement significantly influences employee retention, while organizational culture, in part, also significantly influences employee retention in the foundation. The research's conclusions advance knowledge of the variables influencing worker retention in nonprofits that support women's emancipation. Keywords: Employee Engagement, Organizational Culture, Employee Retention, Woman Empowerment